Morphometry of fruits, seeds and seedlings of Vitex megapotamica (Lamiaceae) - Josiane Otalakosk; Jacqueline Barcelos da Silva; Mariana Salbego Franco; Marina Andressa de Araújo e Silva; Daniele Brandstetter Rodrigues; Andréia da Silva Almeida; Lilian Vanussa Madruga de Tunes (Acta Biológica Catarinense, 2021)
The present study evaluated the morphology and biometry of tarumã fruits and seeds. The experiment was conducted at the Federal University of Pelotas and the fruits were collected in two matrices located in Quedas do Iguaçu – Paraná, in March 2018. The length, width and thickness of fruits and seeds were determined using a digital caliper. For biometric assessments, the arithmetic mean, standard deviation, variation coefficient and the amplitude of the values obtained were calculated. The seed germination process started in approximately 32 days. Throughout the hypocotyl, a color transition was verified. It was observed that the values of length and width of the fruits varied from 15 to 22 mm and 12 to 18 mm, respectively. Regarding the biometry of the seeds, it can be verified that the length, width and thickness of the seeds varied from 5 to 13 mm, 4 to 10 mm and 3 to 7 mm, respectively. As for morphology, it was identified that the species has germination of the epigeal type with protected cotyledon seedlings (phanerocotyledons).